2012
DOI: 10.1128/jvi.07104-11
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Immunization with Virus Replicon Particles Confers Rapid Robust Protection against Rift Valley Fever Virus Challenge

Abstract: c Rift Valley fever virus (RVFV) causes outbreaks of severe disease in people and livestock throughout Africa and the Arabian Peninsula. The potential for RVFV introduction outside the area of endemicity highlights the need for fast-acting, safe, and efficacious vaccines. Here, we demonstrate a robust system for the reverse genetics generation of a RVF virus replicon particle (VRP RVF ) vaccine candidate. Using a mouse model, we show that VRP RVF immunization provides the optimal balance of safety and single-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
5
30
0
Order By: Relevance
“…The dramatic in vivo attenuation of viruses lacking a functional NSs (7,8,18,19) highlights the importance of the early innate response in controlling RVFV replication. Indeed, several of the most promising replication-competent vaccine candidates lack NSs and are associated with an early systemic antiviral response (20) followed by a strong neutralizing antibody response correlating with protection from subsequent challenge with wild-type RVFV (18,(20)(21)(22)(23). These vaccine studies corroborate results from early passive transfer studies with nonhuman primates (24) and mice (25) that indicated protection from RVFV challenge is antibody mediated.…”
Section: Have Roles In Determining Virulence In Vivosupporting
confidence: 76%
See 1 more Smart Citation
“…The dramatic in vivo attenuation of viruses lacking a functional NSs (7,8,18,19) highlights the importance of the early innate response in controlling RVFV replication. Indeed, several of the most promising replication-competent vaccine candidates lack NSs and are associated with an early systemic antiviral response (20) followed by a strong neutralizing antibody response correlating with protection from subsequent challenge with wild-type RVFV (18,(20)(21)(22)(23). These vaccine studies corroborate results from early passive transfer studies with nonhuman primates (24) and mice (25) that indicated protection from RVFV challenge is antibody mediated.…”
Section: Have Roles In Determining Virulence In Vivosupporting
confidence: 76%
“…In this system, wild-type RVFV (Egyptian strain ZH501) infection is uniformly and rapidly lethal, with mice succumbing to fulminant hepatitis 2 to 3 days after infection (20). However, an RVFV strain containing a full-gene deletion of NSs (⌬NSs virus) is highly attenuated in immunocompetent mice and provides an ideal platform for evaluating the role of adaptive immunity in the context of an active innate response.…”
Section: Have Roles In Determining Virulence In Vivomentioning
confidence: 99%
“…The vaccine induced potentially protective (i.e., 1:40), virus neutralizing titers with single vaccination in five of the six animals within 2 weeks pv (Table 1). These results compared favorably with the outcome of recently reported vaccinations using vaccines based on RVFV glycoproteins, such as GnGc VLPs and Gne , de Boer et al 2010, Mandell et al 2010a, Kortekaas et al 2012, Oreshkova et al 2013, as well as a Newcastle disease virus-vectored vaccine (NDFL-GnGc) (Kortekaas et al 2010a, Kortekaas et al 2010b) and virus replicon particles (Dodd et al 2012, Oreshkova et al 2013, some of which have also been reported to elicit neutralizing antibodies with single vaccination in sheep (Kortekaas et al 2010a, Kortekaas, et al 2012, Oreshkova, et al 2013.…”
Section: Discussionsupporting
confidence: 64%
“…Strategies to develop RVFV vaccines include subunit (Schmaljohn et al 1989, Mandell et al 2010a, DNA (Spik et al 2006), viruslike particles (VLPs) , de Boer et al 2010, Kortekaas et al 2012, virus replicon particles (Kortekaas et al 2011, Dodd et al 2012, Oreshkova et al 2013), virus-vectored (Wallace et al 2006, Heise et al 2009) modified live vaccines, developed from recombinant viruses engineered using reverse genetics (Ikegami et al 2006, Bird et al 2008, Billecocq et al 2008, Habjan et al 2008, Bird et al 2011, live attenuated (Smithburn 1949, Caplen et al 1985, Muller et al 1995, Dungu et al 2010, Pittman 2012, Morrill et al 2013, and inactivated whole virus vaccines (Pittman et al 2000). Although subunit vaccines for RVFV are generally considered safe, and recently some progress has been made in their development, evaluation of immunogenicity and/or efficacy in a target species, sheep, has been performed for a few candidates (Kortekaas et al 2012, Oreshkova et al 2013).…”
mentioning
confidence: 99%
“…It was previously proposed that the M segment plays a pivotal role in the copackaging of the L and S segments (20). However, we and others have demonstrated that the M segment is not required for the packaging of L and S genome segments into RVFV replicon particles (23,24), and a two-segmented RVFV that expresses the Gn and Gc genes from the NSs location of the S segment was shown to be viable without an Mtype genome segment (25). Altogether, these studies have provided important new insights into bunyavirus packaging; however, they also made clear that many questions on this topic remain to be answered.…”
mentioning
confidence: 93%